2015
DOI: 10.4238/2015.january.16.10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control and transgressive segregation of zinc, iron, potassium, phosphorus, calcium, and sodium accumulation in cowpea (Vigna unguiculata) seeds

Abstract: ABSTRACT. Cowpea crop, through combining a range of essential minerals with high quality proteins, plays an important role in providing nutritional security to human population living in semi-arid regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…In earlier studies, with other Vigna species like mungbean, an average value of 30.0 and 40.0 mg kg –1 of seed Fe have been reported ( Wu et al, 2020 ), which confirmed that V. stipulacea is the potential source for mitigating Fe deficiency of rural folks especially adolescent children and female with acute problems of anemia. Similarly, the present finding regarding grain Fe concentration was corroborated with the wider variation reported in the case of other small-seeded legumes like lentil ( Thavarajah et al, 2017 ; Kumar et al, 2018 ; Shrestha et al, 2018 ); common bean ( de Araújo et al, 2003 ; Blair et al, 2009 ) and cowpea ( Boukar et al, 2011 ; Santos and Boiteux, 2015 ). On the contrary, a narrow range of variation (20.6–71.0 mg kg –1 ) was reported regarding grain Zn concentration compared to grain Fe in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In earlier studies, with other Vigna species like mungbean, an average value of 30.0 and 40.0 mg kg –1 of seed Fe have been reported ( Wu et al, 2020 ), which confirmed that V. stipulacea is the potential source for mitigating Fe deficiency of rural folks especially adolescent children and female with acute problems of anemia. Similarly, the present finding regarding grain Fe concentration was corroborated with the wider variation reported in the case of other small-seeded legumes like lentil ( Thavarajah et al, 2017 ; Kumar et al, 2018 ; Shrestha et al, 2018 ); common bean ( de Araújo et al, 2003 ; Blair et al, 2009 ) and cowpea ( Boukar et al, 2011 ; Santos and Boiteux, 2015 ). On the contrary, a narrow range of variation (20.6–71.0 mg kg –1 ) was reported regarding grain Zn concentration compared to grain Fe in our study.…”
Section: Discussionsupporting
confidence: 90%
“…This success has paved the way for advances in other pulses. Studies on Fe accumulation traits have been performed on cowpea (Fernandes Santos and Boiteux, 2015 ), chickpea (Diapari et al, 2014 ), pea and lentil (Ray et al, 2014 ), and test trials are currently underway for some of them (HarvestPlus, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The additive effects indicated that the alleles for higher element concentrations were contributed by Ziguangmangluoerling, and that these may be the most important components for enhancing element concentrations through methods of genealogical improvement. Significant additive genetic effects as well as parental mean effects have previously been detected for P, K, Ca, and Na (Fernandes Santos and Boiteux, 2015). Co-localization of QTLs for element concentration has previously been found in various species, such as rice (Yu et al, 2015) and in maize grain (Simić et al, 2012).…”
Section: Qtl Detection and Pleiotropy For Eight Element Concentrationmentioning
confidence: 88%